PENGARUH EDUKASI TERHADAP TINGKAT PENGETAHUAN ANAK TENTANG PENCEGAHAN KARIES GIGI DI SDS HKBP PARDAMEAN MEDAN - Siregar, Cahyani R.; Simanullang, Rostime Hermayerni (STIKes Murni Teguh, 2025)
Dental caries is a common health problem in the community, especially among children. Children are at high risk of developing dental caries due to the habit of freely consuming sweet foods and beverages. Dental caries prevention can begin by increasing children's knowledge, considering that knowledge is one of the factors shaping behavior and actions. One's behavior tends to align with their level of knowledge. Therefore, appropriate education is needed to increase children's knowledge about dental caries prevention. The objective of this study is to analyze effect of education on children's level of knowledge about dental caries prevention at HKBP Pardamean elementary school. The research method is quantitative with a quasi-experimental design using an untreated control group design with dependent pretest and posttest samples. Sampling technique was using a total sampling with 50 respondents. the Wilcoxon signed-rank test Data analysis used. The result of this study indicates that there is a significant effect of education on children's level of knowledge about dental caries prevention with a p-value of 0.00 < 0.05. It can be concluded that there is an effect of education on children's level of knowledge about dental caries prevention at HKBP Pardamean Elementary School Medan in 2024. It is suggested for further research by adding other variables such as behavior to maintain dental health, dental health conditions and eating habit.